2002
DOI: 10.1177/8756087902018003002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Heat Seal Performance of Ionomer Films

Abstract: The heat-seal performance of a flexible plastic package depends on the sealing bar temperature, packaging line speed, film thickness and properties of the sealant resin. For a given sealant, thinner films reach their maximum seal strength at lower bar temperatures and faster line speeds than thicker films. A model is developed that relates these factors to the amount of molecular penetration that develops at the heat-seal interface of ionomer films. A critical value of the penetration is found that corresponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 4 publications
0
32
0
Order By: Relevance
“…As the sealant layer begins to melt, more intimate contact or wetting of the sealing surfaces occurs. Given sufficient time, molecular segments diffuse across the interface forming entanglements, and thus the seal strength increases 4, 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the sealant layer begins to melt, more intimate contact or wetting of the sealing surfaces occurs. Given sufficient time, molecular segments diffuse across the interface forming entanglements, and thus the seal strength increases 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Constant heat sealing has such advantages as low power consumption, high speed, and less stress on the films. However, impulse heat sealing yields stronger and superior appearance of seals 5. In spite of a more complex temperature control, impulse heat sealing is the most widely used technique in vertical fill form seals and horizontal fill form seal packaging operations.…”
Section: Introductionmentioning
confidence: 99%
“…Meka and Stehling [4] also reported that heat seal strength depends primarily on plated temperature and secondary on dwell time. In addition, Morris [9] has confirmed the inverse proportionality relation between platen temperature and dwell time, and has stated that they are influenced by film thickness according to heat transfer theorem. The study of heat seal strength beyond 1 sec dwell time is only of theoretical interest.…”
Section: Effect Of Platen Temperature and Dwell Timementioning
confidence: 99%
“…For instance, Stehling and Meka [5] reported that the T pi value correspond closely to the T mf for all the unsupported polyolefins films investigated in their study. Whilst, Morris [9] reported that the T pi of ionomer films begin after the T mf value. Hence, it can be deduced that laminate films using different sealant materials produces different T pi -T mf trends.…”
Section: Heat Sealing Curvementioning
confidence: 99%
“…In general, homopolymers require less contact time to achieve the maximum seal strength than polymers containing structurally different (heterogeneous) copolymers . The extent of chain penetration between polymer films during heat sealing can be characterized using a dimensionless parameter, as proposed by Morris . This parameter is directly related to the seal strength.…”
Section: Introductionmentioning
confidence: 99%